Penguatan kecerdasan spiritual anak melalui kegiatan tadarus al-quran - Kholid Mawardi; Eka Muawali Nurhayah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
This article explains and describe the implementation of tadarus al-Qur'an activities in the One Day One Juz Community Purbalingga as a strengthening of children’s spiritual intelligence. This type of research used in this research is descriptive qualitative research. From the results of research on Strengthening children’s Spiritual Intelligence through of the Al-Qur'an activities (Case Study of the One Day One Juz Community in Purbalingga), the results show that the mechanism of implementing the tadarus al-Qur'an one day one juz is through the WhatsApp (WA) group and can also go through Black Berry Massanger (BBM). In each group, there are 30 members and there is one admin to monitor the report activities after reading the Qur'an in the group. In addition to the main activity which is tadarus al-Qur'an one day one juz of the ODOJ community also has non tadarus activities. The activity is there to encourage the members of ODOJ to be more strict in reading the Qur'an. These tadarus and non tadarus activities can help strengthen the spiritual intelligence of children members of the ODOJ community.